2015
DOI: 10.3746/jkfn.2015.44.3.442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guar Gum on Quality of Soft Tofu Stew Sauce

Abstract: The aim of this study was to investigate the effects of guar gum on the rheological behaviors, sensory attributes, and consumer acceptability of soft tofu stew sauce. Five different soft tofu stew sauces were commercially manufactured with various levels of guar gum (0.0, 0.1, 0.2, 0.4, and 0.5%). Twelve sensory attributes of the stew sauces were identified by nine trained descriptive panelists, whereas hedonic levels of the stew sauces were assessed by a group of 51 consumers. Steady flow of the stew sauces w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Another possible reason is the different viscosities of the two samples. Im et al [ 55 ] reported that the sensory characteristics of the soft tofu stew sauce seemed to be less perceived for more viscous samples. In this study, the viscosity of the soft tofu stew sauce was higher than that of the vegetable rice porridge (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible reason is the different viscosities of the two samples. Im et al [ 55 ] reported that the sensory characteristics of the soft tofu stew sauce seemed to be less perceived for more viscous samples. In this study, the viscosity of the soft tofu stew sauce was higher than that of the vegetable rice porridge (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The rheometer monitored the steady flow of stew sauces, and the GG-added products exhibited Newtonian behaviors at 0.0%, 0.1%, and 0.2%, while 0.4% and 0.5% exhibited pseudoplastic behaviors. Based on rheological testing, they found that 0.1% of GG-added products were the most popular among consumers It seems that the addition of GG not only influenced rheological properties but also overall acceptability of the stew sauce Im et al (2015) Starch paste Adding GG and xanthan gum to cold-stored starch pastes results in syneresis reduction…”
Section: Meatballmentioning
confidence: 99%
“…Guar gum is also used to provide a smooth texture to products such as doogh (Im et al, 2015 ). Considering the viscosity of the doogh, Pirsa et al ( 2018 ) found that the best conditions were achieved on the first day of the doogh production with 0.1% (w/w) of quince seed mucilage (Qm) and 0.2% (w/w) of GG.…”
Section: Applications Of Guar Gum In the Food Industrymentioning
confidence: 99%
“…However, companies are seeking opportunities to expand their sales to Muslims. Fermented soy-based products such as soy sauce, fermented chili pepper paste ( gochujang ), and fermented soybean paste ( doenjang ) are essential seasoning materials to flavor and characterize traditional Korean cuisine [ 15 , 16 ]. One of these seasonings is almost always applied to flavor foods in Korean cooking.…”
Section: Introductionmentioning
confidence: 99%